Robotics Research The 14th International Symposium ISRR - Pradalier, Cédric; Siegwart, Roland; Hirzinger, Gerhard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This volume presents a collection of papers presented at the 14th International Symposium of Robotic Research (ISRR). ISRR is the biennial meeting of the International Foundation of Robotic Research (IFRR) and its 14th edition took place in Lucerne, Switzerland, from August 31st to September 3rd, 2009. As for the previous symposia, ISRR 2009 followed up on the successful concept of a mixture of invited contributions and open submissions. Half of the 48 presentations were therefore invited contributions from outstanding researchers selected by the IFRR officers, and half were chosen among the 66 submissions after peer review. This selection process resulted in a truly excellent technical program which, we believe, featured some of the very best of robotic research. Out of the 48 presentations, the 42 papers which were finally submitted for publication are organized in 8 sections that encompass the major research orientations in robotics: Navigation, Control & Planning, Human-Robot Interaction, Manipulation and Humanoids, Learning, Mapping, Multi-Robot Systems, and Micro-Robotics. They represent an excellent snapshot of cutting-edge research in robotics and outline future directions.
Part I Navigation -- Part II Control & Planning -- Part III Human Robot Interaction -- Part IV Robotic Manipulation and Humanoids -- Part V Learning -- part VI Mapping -- Part VII Multi-Robot Systems -- Part VIII Micro/Nano Robots.
Keywords: Robotics; Automation; Artificial intelligence; Robotics and Automation; Artificial Intelligence